Eigenvalues of Geometric Operators Under the List's Flow - Ma, Bingqing (Communications in Mathematics and Applications, 2013)
We consider the evolution equation of eigenvalues of the operator $-Δ+cS$ under the (normalized) List's flow. As an application, we derive monotonicity formulas for eigenvalues of $-Δ+\frac{1}{2}S$.
Keywords: Eigenvalue; List's flow; Normalized List's flow